A Burmese taxi in the Black Forest? Stuck mobility and the possibility of dwelling. Issue 1 (2nd January 2020) - Notar, Beth E.; Min, Kyaw San; Gautam, Raju
ABSTRACT: We reformulate Heidegger's question in "Building Dwelling Thinking" to ask – What is the state of dwelling in our precarious and mobile age? – and consider the "politics of dwelling" in relation to the "politics of mobility". Drawing on interviews with taxi cab drivers in Yangon (Rangoon) while stuck in traffic, we argue, drawing on Dwyer's (2009) formulation for waiting, that while the taxi drivers engage in situational dwelling they do not and cannot engage in existential dwelling, due to the environmentally unsustainable "system of automobility" in which they are enmeshed. This article contributes to a discussion of the relationship among im/mobility, dwelling and sustainability, to research within mobility studies on marginalized mobile subjects and to an emerging urban social science within Burma.